STUDIES ON THE IRRITABILITY OF A FIELD POPULATION OF ANOPHELES MACULIPENNIS AND ANOPHELES SUPERPICTUS TO DDT - N. Eshghy (Tehran University of Medical Sciences, 1972)
A series of DDT irritability tests with adult A. maculipennis typicus and A. superpictus were carried out in the Isfahan area in August-September, 1970. The observations on irritability were measured in accordance with the WHO method arid the natural populations of anopheline mosquitoes were used. The tests were carried out in a light intensity of approximately 8 foot candles. The engorged mosquitoes were captured in various villages that had not been treated with DDT since 1964. Note was taken of the number of take-off by anopheline mosquitoes from the impregnated filter paper during a period of 15 minutes. The temperature of the testing room was approximately 25°C.-27°C and the tests were carried out between 9 a.m. and 2 p.m. It was noted that there was a great difference in the average number of take-offs between the control mosquitoes and the mosquitoes exposed to DDT. The average number of take-offs for A. maculipennis exposed to 2% DDT was observed to be between 17.1 and 21, and for 4% DDT, between 25.95 and 26.8; for A. superpictus exposed to 2% DDT, it was between 17.8 and 21. The average number of take-cm-s, for the control group was between zero and one. The levels of irritability for the strains of A.maculipennis and A. superpictus were about the same with no statistically significant difference in irritability for 2% DDT. However, significant difference in irritability was observed with A. maculipennis exposed to 2% and 4% DDT.